Clinical spectrum of cryptogenic organising pneumonitis. Issue 8 (August 1991) - Bellomo, R; Finlay, M; McLaughlin, P; Tai, E
Abstract : Cryptogenic organising pneumonitis (bronchiolitis obliterans organising pneumonia) is an uncommon condition that often responds to steroids. It is characterised clinically by constitutional symptoms, pathologically by intra-alveolar organising fibrosis, and radiologically by patchy pulmonary infiltrates. Its full clinical spectrum and course are only partially described and understood. Six patients are described, seen over three years, with considerably diverse clinical and radiological presentations (two had diffuse lung infiltrates, two had peripheral lung infiltrates, and two had localised lobar involvement) and with very varying severity of disease (two with a life threatening illness, three with appreciable subacute constitutional symptoms, and one with mild symptoms). It is concluded that cryptogenic organising pneumonitis can present in various ways. A set of diagnostic criteria are proposed which will help in the recognition of this syndrome, which is probably underdiagnosed.